ChemInform Abstract: Manganese‐Catalyzed and Promoted Reactions of H‐Phosphinate Esters. Issue 39 (23rd September 2014) - Fisher, Henry C.; Berger, Olivier; Gelat, Fabien; Montchamp, Jean‐Luc
Abstract Manganese catalyzed reactions of H‐phosphinates with various alkenes give the corresponding alkylated products.